Manifestation of Persona Dealing with Misogyny as Reflected in Qahera the Superhero - Riana Permatasari; Destary Praptawati (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
Nowadays, there are a growing number of Muslim woman superheroes in literature; one of them is a webcomic entitled Qahera the Superhero. Qahera is portrayed as a veiled Eqyptian woman superhero dealing with misogyny throughout the story. This study is a qualitative study aimed at finding the manifestation of persona as reflected in Qahera and its relation to misogyny. In collecting the data, there were three steps taken, including reading the webcomic, identifying the data, and classifying the data in a table consisting of the data, the page/part of the comics, the references supported the data, and the analysis. The collected data were analyzed using the theory about persona by Carl Jung as the underlying theory in this study. Based on the research, there are two points concluded. First, the outward manifestation of persona in Qahera is a woman superhero wearing a hijab who is strong and brave. Second, her persona is built to fulfill society's expectations on how a woman should wear and protect women from misogyny in her community. She fights against misogyny by challenging the negative stereotypes about Muslim women, combating sexual harassment, and not supporting misogyny in various forms, including in arts. In short, Qahera built her persona to protect Muslim women and showed the persona manifestation of how a woman superhero can challenge the negative stereotypes of Muslim women without neglecting Islamic values inside her.